The Characteristics of Land Use in Kemiri-based Agroforestry Patterns in Maros Regency, South Sulawesi Province - Andi Khairil A.Samsu (Jurnal Penelitian Kehutanan BONITA, 2023)
One of the leading causes of global warming is land damage due to forest encroachment and the conversion of forest areas. One of the efforts to reduce the increase in greenhouse gas concentrations is maintaining carbon reserves by developing and improving forest vegetation. The agroforestry pattern can solve problems from both environmental and economic aspects in society. Candlenut plants are one of several types of plants that are usually used by applying the agroforestry model. Cenrana, Camba, Mallawa Districts, and Maros Regency are still developing and utilizing candlenut plants on community-owned land and in forest areas. This study aims to determine the spatial characteristics of the candlenut-based agroforestry pattern in Maros Regency. This research uses a quantitative method using remote sensing technology based on Google Earth Engine (GEE). The results of the study show that the agroforestry pattern in Maros Regency (Mallawa District, Camba District, Cenrana District) applies the Agrisilvicultural and Silvipastural patterns, apart from that the community's candlenut agroforestry land is located at a distance that can be reached by the community, namely 0-2 km outside the forest area. The composition of candlenut-based agroforestry and non-agroforestry patterns shows several crop combinations: horticulture, food, and plantations.